2014
DOI: 10.1105/tpc.113.121566
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Regulates Early Seed Development in Arabidopsis by ABI5-Mediated Transcription of SHORT HYPOCOTYL UNDER BLUE1

Abstract: Seed development includes an early stage of endosperm proliferation and a late stage of embryo growth at the expense of the endosperm in Arabidopsis thaliana. Abscisic acid (ABA) has known functions during late seed development, but its roles in early seed development remain elusive. In this study, we report that ABA-deficient mutants produced seeds with increased size, mass, and embryo cell number but delayed endosperm cellularization. ABSCISIC ACID DEFICIENT2 (ABA2) encodes a unique short-chain dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 64 publications
7
147
1
2
Order By: Relevance
“…In barley (Hordeum vulgare), decreased ABA content causes abnormal endosperm development, including abnormal cellularization/ differentiation of endosperm (Sreenivasulu et al, 2010). Recent studies showed that the ABA-deficient mutant aba2-1 presents delayed endosperm cellularization (Cheng et al, 2014), suggesting that ABA promotes cellularization, which is consistent with our finding revealing the up-regulation of ABA responserelated genes during rice endosperm cellularization. The expression of a DUF1264 domain-containing protein (LOC_Os05g49440) during cellularization is regulated by methylation, and the phosphorylation state of its homolog in Arabidopsis is modulated by ABA (Ghelis et al, 2008), which suggests a possible role of LOC_Os05g49440 in cellularization in response to ABA.…”
Section: Complex Regulation Of Endosperm Cellularizationsupporting
confidence: 93%
“…In barley (Hordeum vulgare), decreased ABA content causes abnormal endosperm development, including abnormal cellularization/ differentiation of endosperm (Sreenivasulu et al, 2010). Recent studies showed that the ABA-deficient mutant aba2-1 presents delayed endosperm cellularization (Cheng et al, 2014), suggesting that ABA promotes cellularization, which is consistent with our finding revealing the up-regulation of ABA responserelated genes during rice endosperm cellularization. The expression of a DUF1264 domain-containing protein (LOC_Os05g49440) during cellularization is regulated by methylation, and the phosphorylation state of its homolog in Arabidopsis is modulated by ABA (Ghelis et al, 2008), which suggests a possible role of LOC_Os05g49440 in cellularization in response to ABA.…”
Section: Complex Regulation Of Endosperm Cellularizationsupporting
confidence: 93%
“…ARF2 negatively regulates the expression of ANT, consequently ANT directly regulates the function of COR15A to regulate seed mass and stress resistance. The ARF2-ANT-COR15A-ABA-mediated signal cascade that we have identified in this study might be different from that which regulates seed development through the SHB1-ABAmediated pathway, which has been proposed by Cheng et al (2014).…”
Section: Discussionmentioning
confidence: 70%
“…Studies have identified that the ABA2, ABI5 and SHB1 genes are involved in controlling seed size (Cheng et al, 2014). Specifically, ABA2 is positively regulated upon ABA accumulation, activating ABI5 in ABA signaling, consequently negatively modulating SHB1 The intensity of GUS coloration was quantified by using Adobe Photoshop CS (Adobe Systems) software, as described by Wang et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…SAB5300167). Finally, the precipitated DNA fragments were analyzed using RT-qPCR as described previously (Cheng et al, 2014;Zhou et al, 2009). Tissues derived from different plants were used in distinct biological replicates.…”
Section: Chip Assaymentioning
confidence: 99%